Câu 1 a,cho biểu thức :(3x-5).(2x+11)-(2x+3).(3x+7) Câu 2 Tìm x biết: a,(3x+5).(2x-1)+(5-6x).(x+2)=x b,(5x-3).(7x+2)-35x(x-1)=42 Câu 2 a,Giá trị x

Question

Câu 1
a,cho biểu thức :(3x-5).(2x+11)-(2x+3).(3x+7)
Câu 2 Tìm x biết:
a,(3x+5).(2x-1)+(5-6x).(x+2)=x
b,(5x-3).(7x+2)-35x(x-1)=42
Câu 2
a,Giá trị x thoả mãn (10x+9).x-(5x-1)(2x+3)=8
b, Giá trị x thoả mãn x(x+1)(x+6)-x³=5x
c, Giá trị x thoả mãn 2x²+3(x-1)(x+1)=5x(x+1)

in progress 0
Melanie 1 năm 2021-12-02T07:00:45+00:00 1 Answers 2 views 0

Answers ( )

    0
    2021-12-02T07:01:49+00:00

    C1:

    `(3x-5)(2x+11)-(2x+3)(3x+7)`
    `=6x^2+33x-10x-55-(6x^2+14x+9x+21)`
    `=6x^2+33x-10x-55-6x^2-14x-9x-21`
    `=76`

    C2:

    a, `(3x+5)(2x-1)+(5-6x)(x+2)=x`
    `<=>6x^2+7x−5+(−6x^2−7x+10)=x`
    `<=>6x^2+7x−5−6x^2−7x+10=x`
    `<=>5=x`
    `<=>x=5`

    b, `(5x-3)(7x+2)-35x(x-1)=42`
    `<=>35x^2−11x−6-(35x^2−35x)=42`
    `<=>35x^2−11x−6-35x^2+35x=42`
    `<=>24x-6=42`
    `<=>24x=48`
    `<=>x=2` 

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )